Clinical Comparison of a Silicone Hydrogel and a Conventional Hydrogel Daily Disposable Contact Lens - Miller J (Dove Medical Press, 2021)
Jason Miller,1 Bradley Giedd,2 Lakshman N Subbaraman3 1EyeCare Professionals of Powell, Powell, OH, USA; 2Maitland Vision Center, Maitland, FL, USA; 3Alcon Research, LLC, Johns Creek, GA, USACorrespondence: Jason MillerEyeCare Professionals of Powell, 9711 Sawmill Parkway, Powell, OH, 43065, USATel +1 614 793-0700Fax +1 614 793-0084Email millereyedoc@me.com; drmiller@eyecarepowell.comPurpose: To compare the subjective performances of verofilcon A daily disposable silicone hydrogel contact lenses (CLs) and etafilcon A hydrogel CLs.Methods: Successful wearers of spherical soft CLs for distance correction were prospectively randomized to wear verofilcon A or etafilcon A lenses for 1 week and crossed over to the alternative lenses. The primary study objective was a comparison of distance visual acuity (VA). Exploratory endpoints included subjective overall lens preference (5-point scale) and subjective ratings (10-point scales) of end-of-day (EOD) vision, overall handling, insertion comfort, EOD comfort, overall quality of vision, overall comfort, vision throughout the day, lens handling at insertion, and lens handling at removal.Results: Of 92 subjects (184 eyes), 46 each were randomized to verofilcon A or etafilcon A lenses and subsequently crossed over to the other lenses. Evaluation of distance VA showed that verofilcon A lenses were noninferior to etafilcon A lenses. Comparison of lens preference showed that 68 (73.9%) subjects somewhat or strongly preferred verofilcon A lenses, whereas 21 (22.9%) somewhat or strongly preferred etafilcon A lenses (p< 0.0001). Mean ± SD ratings of EOD vision (8.6± 1.5 vs 7.7± 1.9), overall handling (8.7± 1.5 vs 6.9± 2.3), insertion comfort (9.2± 1.0 vs 7.7± 1.9), and EOD comfort (8.0± 1.9 vs 7.0± 2.2) were all significantly (p≤ 0.0001 each) higher for verofilcon A than for etafilcon A lenses. Mean ± SD ratings of overall quality of vision (8.9± 1.2 vs 8.2± 1.8), overall comfort (8.6± 1.5 vs 7.4± 1.8), vision throughout the day (8.9± 1.3 vs 8.1± 1.8), lens handling at insertion (9.0± 1.4 vs 6.9± 2.5), and lens handling at removal (8.3± 2.1 vs 7.7± 2.2) were also significantly higher for verofilcon A lenses. No subject experienced any ocular adverse events.Conclusion: After 1 week of wear, the study population reported that ratings for subjective endpoints were significantly higher for verofilcon A lenses than for etafilcon A lenses.Keywords: etafilcon A, subjective, verofilcon A, visual acuity